Technological integration within zakat institutions: a comprehensive review and prospective research directions - Aisyah Abdul-Rahman,; Shifa Mohd Nor,; Salmy Erdawati Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research undertakes a meticulous systematic literature review on the integration of technology within zakat institutions. With the surge in technological advancements, these institutions stand to reap significant benefits, particularly regarding the digital management practices in zakat collection and distribution. This review amalgamates various research methodologies and guided by the ROSES (RepOrting standards for Systematic Evidence Syntheses) publication standard. We selected articles from two foremost databases, SCOPUS and Web of Science, for this study. Thematic analysis yielded two principal themes: the fundamental understanding of digital zakat, and; practices of digital management. The former theme encompasses seven sub-themes (awareness, trust, perceived risk, personal innovativeness, information integration, technology implementation, and efficiency), while the latter is divided into two sub themes, namely digital collection and distribution procedures. Our findings underscore the significance of implementing technology in managing zakat and present a roadmap for future research in this area. This study contributes to the existing body of literature by examining the adoption of technology in the field of Islamic social finance research.